1982
DOI: 10.1016/0035-9203(82)90007-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma albumin, parasitic infection and pubertal development in Egyptian boys

Abstract: Pubertal stage was assessed in 453 Egyptian boys aged from nine to 17 years. Weights and albumin concentrations were measured and parasites identified from stool samples. The mean age to reach each stage of puberty was significantly delayed in the presence of low albumin levels and parasites. The magnitude of the delay was greater for genital stage 2 than for later stages. Weight was also lower in children with reduced albumin concentration or parasites. Among children of the same age, weight and albumin were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The reversibility of this outcome is unclear, although Smith et al (1975) reported that chronically undernourished adult Indian males manifested significantly lower testosterone increases in response to gonadotropin stimulation despite a month of refeeding, suggesting permanent Leydigcell insensitivity. Other factors, such as immunological and psychological stress, may also influence pubertal hormone receptor priming (Cole et al, 1982;Nottelmann et al, 1987;Ratner Kaufman et al, 1997;Spratt et al, 1993), but further investigation is necessary. For biological anthropologists interested in the timing and characteristics of crucial life history events such as sexual maturation, understanding the pubertal establishment of adult reproductive hormone function is an important step in characterizing the evolution of male reproductive strategies.…”
Section: Reproductive Endocrinologymentioning
confidence: 99%
“…The reversibility of this outcome is unclear, although Smith et al (1975) reported that chronically undernourished adult Indian males manifested significantly lower testosterone increases in response to gonadotropin stimulation despite a month of refeeding, suggesting permanent Leydigcell insensitivity. Other factors, such as immunological and psychological stress, may also influence pubertal hormone receptor priming (Cole et al, 1982;Nottelmann et al, 1987;Ratner Kaufman et al, 1997;Spratt et al, 1993), but further investigation is necessary. For biological anthropologists interested in the timing and characteristics of crucial life history events such as sexual maturation, understanding the pubertal establishment of adult reproductive hormone function is an important step in characterizing the evolution of male reproductive strategies.…”
Section: Reproductive Endocrinologymentioning
confidence: 99%
“…91 Within a cross-sectional study of parasitic infection in 453 Egyptian boys, Entamoeba hystolytica infection was inconsistently associated with later genitalia development (observed in G2, G4 and G5 stages) compared with non-infected boys. 93 There was no association with overall parasitemia or other individual parasites whose prevalence ranged from 1 to 14% compared with E. hystolytica prevalence of 32-51%. Contrast to the findings with breast development, there was no association between the number of hospital admissions due to infection and genitalia development in 3985 Chinese boys.…”
Section: Resultsmentioning
confidence: 81%
“…Of the 15 epidemiology studies, outcomes were prospectively ascertained in five 80,88,89,91,92 and elicited in a cross-sectional manner at the same time as infection exposure status, in 10. 90,[93][94][95][96][97][98][99][100][101] Physical pubertal characteristics were measured using Tanner and Marshall staging which uses line drawings showing five stages from Tanner stage T1-T5, with stage T2 marking the onset of pubertal development and stages T3-T5 marking increasing maturity. 102,103 With one exception where age at menarche was determined through medical records, 92 the start of menarche was recalled by study participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations